PERANAN KOMUNIKASI KELUARGA PADA PERKEMBANGAN REMAJA DI KELURAHAN SARIO KOTA MANADO - Mewengkang, Norma (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: one of the factors that support the occurrence of teenagers fall in the negative Association ofparents are too busy working or busy with activities each so there is no more time to build a goodcommunication with their teenage children who desperately need their guidance. The purpose of thisresearch is to find out How the communication role of the Family in the development of Teenagers inKelurahan Sario Manado.The methods used in this research is descriptive methods, descriptive methods, namely thetroubleshooting procedures provided by describing or depicting the State of the subject or the objectof a good research, public institutions and others at the same time based on the same facts. Thepopulation in this study are all the teens that are on the Wards Sario Manado by the numberof samples taken 20% of the population, namely 32 32 teenagers and parents who are in Ward SarioManado.The results showed family Communication plays a role in the development of teenagers in urban villageSario Manado where it is supported by aspects of the personality which is assumption and behavior thatwe receive from our parents or the people we consider to our parents. Communication between parentsand children can lead to the development of the adolescents were positive.Key Words: Role, Family Communication, The Development of Adolescents